Hepatitis C Seropositivity and Kidney Function Decline Among Women With HIV: Data From the Women's Interagency HIV Study - Tsui, Judith (2009)
BACKGROUND: How co-infection with hepatitis C virus (HCV) impacts on the trajectory of kidney function among HIV-infected patients is unclear. This study examined the effect of HCV on kidney function over time among women infected with HIV. STUDY DESIGN: Retrospective observational cohort SETTING AND PARTICIPANTS: Study sample included participants from the Women's Interagency HIV Study who were HIV-infected and had received HCV antibody testing and serum creatinine measurement at baseline. PREDICTOR: HCV seropositivity OUTCOMES AND MEASUREMENT: Estimated glomerular filtration rate (eGFR) calculated from semi-annual serum creatinine measurements using the 4-variable Modification of Diet in Renal Diseases (MDRD) Study equation. Linear mixed models were used to evaluate the independent effect of being HCV seropositive on eGFR over time, adjusting for demographic factors, co-morbid conditions, illicit drug use, measures of HIV disease status, use of medications, and interactions with baseline low eGFR (<60 mL/min/1.73m(2)). RESULTS: Of the 2,684 HIV-infected women, 952 (35%) were found to be HCV seropositive. For 180 women with CKD at baseline (eGFR <60 mL/min/1.73m(2)), being HCV seropositive was independently associated with a fully-adjusted net decline in eGFR of about 5% per year (95% CI: 3.2 to 7.2%), relative to women who were seronegative. In contrast, HCV was not independently associated with decline in eGFR among women without low eGFR at baseline (p<0.001 for interaction). LIMITATIONS: The MDRD Study equation has not been validated as a measure of GFR among persons with HIV or HCV. Proteinuria was not included in the study analysis. Because the study is observational, the effects of residual confounding cannot be excluded. CONCLUSIONS: Among HIV-infected women with CKD, co-infection with HCV is associated with a modest, but statistically significant decline in eGFR over time. More careful monitoring of kidney function may be warranted for HIV-infected patients with CKD who are also co-infected with HCV.